2020
DOI: 10.1111/tan.13806
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐E genotyping and its relevance in kidney transplantation outcome

Abstract: HLA-E, a class I nonclassical HLA molecule, is expressed in all tissues and is involved in the regulation of both innate (by interaction with the CD94/NKG2 receptor expressed mainly in NK cells) and adaptive immunity (by interaction with T CD8 + cells), suggesting a possible role in the solid organ transplantation context. Transplanted patients with chronic kidney disease and their respective donors (N = 107 pairs) were genotyped for exons 2 and 3 of the HLA-E locus by sequence-based typing (SBT). Groups' geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The role of this functional dimorphism of HLA-E in solid organ transplantation has been studied in only a very limited number of studies. One study showed a protective role of the HLA-E*01:01/01:01 genotype of the donor for rejection in 107 kidney transplantation donor-recipient pairs ( 131 ). In another study, living-donor kidney recipients with HLA-E*01:01/01:01 experienced less BK polyoma virus (BKPyV) reactivation than recipients with other genotypes, and BKPyV-induced nephropathy occurred more frequently in recipients carrying the HLA-E*01:03 allele ( 132 ).…”
Section: Non-classical Hla Class I Molecules As Ligands For Nk Cell Receptors In Kidney Transplantationmentioning
confidence: 99%
“…The role of this functional dimorphism of HLA-E in solid organ transplantation has been studied in only a very limited number of studies. One study showed a protective role of the HLA-E*01:01/01:01 genotype of the donor for rejection in 107 kidney transplantation donor-recipient pairs ( 131 ). In another study, living-donor kidney recipients with HLA-E*01:01/01:01 experienced less BK polyoma virus (BKPyV) reactivation than recipients with other genotypes, and BKPyV-induced nephropathy occurred more frequently in recipients carrying the HLA-E*01:03 allele ( 132 ).…”
Section: Non-classical Hla Class I Molecules As Ligands For Nk Cell Receptors In Kidney Transplantationmentioning
confidence: 99%
“…The potential impact of this dimorphism has been studied for various diseases with inconsistent results 8,10 . In kidney transplantation, HLA‐E*01:01 homozygosity of the recipient and/or donor seems to be favorable 11,12 . Recently, the dimorphism's influence on hematopoietic stem cell transplantation has been analyzed in 1840 patients.…”
Section: Introductionmentioning
confidence: 99%